Olive Drab in Black and White: the brazilian expeditionary Force, the US army and racial national identity - Uri Rosenheck (Esboços)
When the Brazilian Expeditionary Force arrived in Italy to fight alongside the Allies in WWII, its members were introduced to the racially segregated US Army. Based on memoirs, published oral testimonies, newspapers, and comics, this paper explores the ways in which Brazilians of all walks of life—rather than ideology-producing elites—projected their own perceptions on race relations and what it meant racially to be a Brazilian. Their representations, however, were not uniform. Rather, they offered an array of alternative racial national identities varying from whole-white troops to zealous support of their “Racial Democracy.” Civil rights activists in the United States used these images to condemn their domestic racial segregation while some Brazilians criticized the Brazilian army’s hypocrisy and racism.